Evaluation of an Innovative Incisional Dressing With Closed Incisional Negative Pressure Wound Therapy System in Healthy Volunteers Through Evaluation of Dressing Survivability, Adverse Reactions, User Tolerability, and Comfort: A Self-controlled Randomized Trial in Healthy Volunteers - Jennifer Stocks; Kelly Nunn; Casey Young Carter; Timothy Oetter; Ethan Valentine; Jonathan Matthew Cayce (Advances in Skin & Wound Care, 2026)
OBJECTIVE: This study compared an innovative closed-incision negative pressure wound therapy (ciNPWT) system with the leading control system in healthy volunteers simulating recovery from total knee arthroplasty. The new system combines a single-use NPWT device with an incisional dressing designed to reduce skin irritation and blistering. Outcomes included dressing survivability, skin irritation, discomfort, and nuisance. METHODS: Healthy volunteers aged 40 to 80 were recruited. After surgical skin preparation, each participant had one knee randomized to the evaluated system and the other to the control system. Participants wore both systems for up to 7 days unless an adverse event occurred. Discomfort and tolerance were rated daily on a 10cm Visual Analog Scale, and a blinded clinician assessed skin irritation at dressing removal using a standardized scale. RESULTS: Sixteen healthy volunteers participated. Dressing survivability did not differ significantly between systems ( P = .081). The evaluated system produced lower skin irritation scores than the control system ( P = .015; 95% CI, −5 to −1). Continuous ordinal regression showed lower discomfort with the evaluated system on days 5 to 7 and lower nuisance on day 7. CONCLUSIONS: The ciNPWT system provided similar dressing survivability while reducing adverse skin reactions.